Serum Osteocalcin and Testosterone Concentrations in Adult Males with or without Primary Osteoporosis: A Meta-Analysis. (2nd August 2017) - Liu, Zhong-Yu; Yang, Yang; Wen, Chun-Yi; Rong, Li-Min
Abstract : Osteocalcin (Ocn) and testosterone play important roles in male skeleton. However, the concentrations of serum osteocalcin and testosterone have never been systematically compared between populations with and without primary male osteoporosis, a common skeletal disorder in adult males. We searched the PubMed, Embase, and Cochrane Library for relevant studies. A meta-analysis was performed to compare the serum osteocalcin and testosterone concentrations between primary osteoporotic males and age-matched nonosteoporotic (non-OP) males. Five case-control studies with 300 adult males were included. We found no significant difference between cases and controls in serum total osteocalcin (TOcn) [95% confidence interval (CI): −1.25, 1.31; p = 0.96 ] and total testosterone (TT) concentrations [95% CI: −0.88, 4.22; p = 0.20 ]. The level of evidence of this carefully performed meta-analysis is 3a according to Oxford (UK) CEBM Levels of Evidence. Future well-designed studies with larger sample size and better standardization of Ocn assay are awaited to confirm and update our current findings.